Modulation of the Effective Metal‐Support Interactions for the Selectivity of Ceria Supported Noble Metal Nanoclusters in Atmospheric CO 2 Hydrogenation - Guo, Yu; Liu, Zongyuan; Zhang, Feng; Wang, De‐Jiu; Yuan, Kun; Huang, Ling; Liu, Hai‐Chao; Senanayake, Sanjaya D.; Rodriguez, Jose A; Yan, Chun‐Hua; Zhang, Ya‐Wen (ChemCatChem, 2021)
Ever‐increasing attention is paid to the sustainable utilization of CO 2 in the atmosphere out of environmental and economic considerations. The deep‐going clarification of the effective and ineffective metal‐support interactions (MSI) in the supported catalysts for the catalytic performance of CO 2 hydrogenation is particularly needed to design highly active nanocatalysts. How to tune the MSI to be effective for the selectivity of goal hydrogenation products is a significant but rather challenging subject. In this work, we demonstrate that the selectivity in CO 2 hydrogenation can be regulated from preferential CH 4 production to preferential CO production by varying the nature of the electronic MSI for ceria supported noble metal nanoclusters, and the effective MSI play a pivotal role for the catalytic systems with opposite hydrogenation selectivity. The modulation of the effective MSI for the selectivity in CO 2 hydrogenation sheds new light on the comprehensive understanding of the MSI and interfacial effects in terms of tailoring and controlling the performance of supported heterogeneous catalysts.